The Difference between Money Laundering and Procuring - Radu Ștefănuț (EIRP Proceedings, 2021)
The study is a critical-analytical approach regarding the judicial practice, the author analyzing and presenting the arguments underlying the determination of criminal liability in the situation of acquiring material goods from the practice of prostitution. The conclusion drawn consists in determining the criteria that must be considered upon the legal classification of this crime. This study was determined by the change of orientation of the criminal policy on the part of the Romanian legislator regarding criminalization of procuring and prostitution, as well as relating the current legal situation to the offense of money laundering.